Bioactive Compounds, Antioxidant, and Antimicrobial Activity of Seeds and Mucilage of Non-Traditional Cocoas - Elena Coyago-Cruz; Iván Salazar; Aida Guachamin; Melany Alomoto; Marco Cerna; Gabriela Mendez; Jorge Heredia-Moya; Edwin Vera (Antioxidants)
The biodiversity of the Amazon rainforest includes little-known cocoa species, which are essential resources for local communities. This study evaluated the bioactive compounds and antioxidant and antimicrobial activity of seeds and mucilage of four non-traditional cocoa species (Theobroma subincanum, T. speciosum, T. bicolor and Herrania nitida). Physico-chemical properties, minerals, vitamin C, organic acids, phenolics, and carotenoids were analysed by spectrophotometric and chromatographic techniques. The antioxidant activity was measured by ABTS and DPPH, along with the antimicrobial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Streptococcus mutans, as well as Candida albicans and Candida tropicalis. T. subincanum seeds scored high in titratable acidity, magnesium, sodium, syringic acid, chlorogenic acid, caffeic acid, rutin, and quercetin. In contrast, the mucilage scored high in calcium, m-coumaric acid, ferulic acid, kaempferol, quercetin glycoside, and antimicrobial activity against Streptococcus mutans. T. speciosum mucilage excelled in malic acid, tartaric acid, naringenin, and antioxidant capacity. T. bicolor seeds excelled in lutein and antimicrobial activity against Staphylococcus aureus and Candida albicans, and mucilage in iron, potassium, vitamin C, citric acid, gallic acid and 4-hydroxybenzoic acid, zeaxanthin, β-carotene, and antioxidant capacity by ABTS. The mucilage of H. nitida has a high soluble solids content. These results highlight the potential of these species as sustainable sources of functional compounds and nutraceuticals.